IMPLEMANTION OF PROBLEM BASED LEARNING (PBL) MODEL TO IMPROVE STUDENT’S MOTIVATION IN CLASS X PHARMACY SMK NEGERI 8 BATAM - Tesa, Karmila (Journal of Educational Studies, 2023)
The learning model is very important in supporting the success of learning and teaching process; therefore the teacher as an educator must master and understand the appropriate learning model with the character of students. The writer in this case as a teacher applies the Problem Based Learning (PBL) learning model in teaching English in class X Pharmacy because the writer realizes that this model is very appropriate to the character of students. By using this model, students are more enthusiastic and active in the learning process.